Pengaruh Profitabilitas dan Pertumbuhan Penjualan terhadap Manajemen Laba dengan Financial Distress sebagai Variabel Mediasi - Tsalisa Binti Mudhawamah; Putri Awalina; Fitria Magdalena Suprapto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine the effect of profitability (X1) and sales growth (X2) on earnings management (Y) with financial distress (Z) as a mediating variable. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange for the period 2020-2023. The sampling technique for this study used purposive sampling so that a total of 92 data could be processed. The data analysis technique in this study uses path analysis using SPSS software version 25. The results showed that profitability has a negative effect on earnings management and sales growth has a positive effect on earnings management. Profitability has a positive effect on financial distress, while sales growth has no effect on financial distress. Financial distress has a positive effect on earnings management. The results of the mediating variable test using path analysis show that financial distress is able to mediate the effect of profitability on earnings management, while financial distress is unable to mediate the effect of sales growth on earnings management.